High-skid-resistance IXPE foam for electronic screen packaging and preparation method of high-skid-resistance IXPE foam

By introducing maleic anhydride grafted elastomer and alkenyl quaternary phosphonium salt into polyethylene foam, and using electronic radiation crosslinking and high-temperature foaming technology, the problems of poor anti-slip performance and electrostatic hazard of traditional IXPE foam are solved, and high anti-slip and anti-static IXPE foam materials are realized, suitable for electronic screen packaging.

CN119570140APending Publication Date: 2025-03-07ZHEJIANG WANLI NEW MATERIALS TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411875331.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

Traditional IXPE foam has poor anti-slip performance in electronic screen packaging, and the addition of a large amount of conductive carbon black will reduce mechanical properties and damping and shock absorption performance, while it cannot avoid static hazards.

Method used

By introducing maleic anhydride grafted elastomer and alkenyl quaternary phosphonium salt into polyethylene foam, combined with electron radiation crosslinking and high temperature foaming technology, a high anti-slip and anti-static IXPE foam material is formed.

Benefits of technology

It achieves high anti-slip, anti-static properties and good mechanical properties, and is suitable for electronic screen packaging to ensure anti-slip buffering and anti-static requirements during transportation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2ZVIRDTNH5SQU4F2UTG8NDDVON7T6FGS6XYEPGJV
    Figure 2ZVIRDTNH5SQU4F2UTG8NDDVON7T6FGS6XYEPGJV
  • Figure APBPGYQUBD62RCRMU4RDOIGCMTOL7X1T6AJPHUMO
    Figure APBPGYQUBD62RCRMU4RDOIGCMTOL7X1T6AJPHUMO
  • Figure M5B0XCDRRWZ0TAZ2IWIN9SFDSXX2CHMBCCKT4AUS
    Figure M5B0XCDRRWZ0TAZ2IWIN9SFDSXX2CHMBCCKT4AUS
Patent Text Reader

Abstract

The invention discloses a high-skid-resistance IXPE foam material for electronic screen packaging and a preparation method thereof.According to the method, a maleic anhydride grafted elastomer and a quaternary phosphonium salt functional component are added, the skid resistance of a product is improved through the maleic anhydride grafted elastomer, the antistatic performance of the product is improved through the quaternary phosphonium salt component, an antistatic agent is connected into a polyethylene network through alkenyl, and the high-skid-resistance IXPE foam material is obtained. The problems of migration, precipitation and decline of a traditional micromolecule antistatic agent are avoided, and the anti-skid buffering and antistatic requirements of precise electronic screen packaging are greatly guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a highly anti-slip IXPE foam for electronic screen packaging and a preparation method thereof. Background Art

[0002] Radiation cross-linked polyethylene foam is a new type of foamed plastic with a closed-cell structure between soft (polyurethane) and hard (polystyrene) foam plastics. It has a series of properties such as superior strength, toughness, elasticity, flexibility, wear resistance, chemical corrosion resistance, low temperature resistance and good insulation. It can be used as a good insulating, heat-insulating, shock-proof and buoyancy material, and is widely used in various fields such as industry, agriculture, construction and transportation.

[0003] IXPE foam products are used as cushioning materials in the packaging of precision electronic screens. Since electronic screens are prone to vibration and slippage during transportation, direct hard contact between screens can cause scratches on the product surface and damage to the LCD screen. Therefore, the anti-slip property of the product is very important. Since polyethylene is a non-polar molecule, its piezoelectric voltage is very strong and it is very easy to generate high-voltage static electricity, which can harm equipment. Therefore, the anti-static property of the material is also very important.

[0004] Traditional IXPE foam generally improves the antistatic property of the product by adding conductive carbon black, but the use of a large amount of conductive carbon black will greatly reduce the mechanical properties and damping and shock absorption properties of the product, and only black products can be selected. Its anti-slip performance is poor, and it is easy to vibrate and slip during the transportation of electronic screens, causing scratches on the screen surface, screen damage and other problems. In response to the above problems, a solution is proposed below. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a highly anti-skid IXPE foam for electronic screen packaging, which has the advantages of good antistatic performance and anti-skid buffering performance.

[0006] The above technical objectives of the present invention are achieved through the following technical solutions: A highly anti-slip IXPE foam for electronic screen packaging, comprising the following material components in parts by weight: 40-90 parts low density polyethylene 10-30 parts of maleic anhydride grafted elastomer 10-25 parts of alkenyl quaternary phosphonium salt 10-30 parts thermoplastic elastomer 1 to 5 parts of sensitizer 2-20 parts of azodicarbonamide foaming agent 0.5-4 parts of antioxidants; After the above components are mixed, they are added into a screw extruder for mixing and extrusion to obtain a master sheet; the master sheet is cross-linked by electron irradiation, and after the electron irradiation cross-linking is completed, the obtained material is subjected to high-temperature foaming treatment to obtain a high-anti-slip IXPE foam material for electronic screen packaging.

[0007] Preferably, the low-density polyethylene is General low-density polyethylene with a density of 0.901~0.922g / cm3 and a melt index of 1~6 g / 10 min, Linear low-density polyethylene with a density of 0.905~0.930g / cm3 and a melt index of 0.3~5g / 10 min, One or more ultra-low density polyethylenes with a density of 0.880-0.910 g / cm3 and a melt index of 0.35 g / 10 min.

[0008] Preferably, the maleic anhydride grafted elastomer is one or more of EPDM rubber, ethylene-octene copolymer, ethylene-hexene copolymer, ethylene-butene copolymer, ethylene-vinyl acetate copolymer, natural rubber, isobutyl rubber, styrene-butadiene rubber, styrene-butadiene block copolymer, and pentylbenzene block copolymer.

[0009] Preferably, the antioxidant is Pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate 1,1,3-Tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane, 1,3,5-Trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, Any one or more of butylated hydroxyanisole, butylated hydroxytoluene, propyl gallate, and tert-butylhydroquinone.

[0010] Preferably, the sensitizer is one or more of zinc stearate and zinc oxide.

[0011] A method for preparing a highly anti-skid IXPE foam for electronic screen packaging, using maleic anhydride grafted elastomer and alkenyl quaternary phosphonium salt functional components to prepare a highly anti-skid and antistatic IXPE foam material, comprising the following steps: S1: Synthesis of maleic anhydride grafted elastomer 100 parts of thermoplastic elastomer, 10-20 parts of maleic anhydride and 1 part of azobisisobutyronitrile were mixed in a mixer at 130°C for 2 hours, and pelletized and extruded to obtain a maleic anhydride grafted elastomer; S2: Synthesis of alkenyl quaternary phosphonium salts Tributylphosphine and alkenyl halide in equal molar ratio are heated at 100-150°C, reacted for 4-12 hours, filtered, washed with ethyl acetate and dried to obtain the corresponding alkenyl quaternary phosphonium salt antistatic component; S3: Preparation of polyethylene foam The maleic anhydride grafted elastomer, alkenyl quaternary phosphonium salt, polyethylene, thermoplastic elastomer, antioxidant, azodicarbonamide, zinc stearate, etc. are uniformly mixed in a mass ratio of 10-30:10-25:40-90:10-30:0.5-4:2-20:1-5, and then added into a single screw extruder for extrusion, and the extrusion temperature is controlled to be 95-130°C, the screw speed is 6-25rpm, and the die head temperature is 90-130°C to obtain a mother sheet with a certain thickness; The master sheet is passed through an electron accelerator for irradiation cross-linking, and the irradiation dose is controlled to be 5 to 50 kGy to form a cross-linked polymer network to obtain a cross-linked master sheet; The cross-linked mother sheet is placed in a foaming furnace for foaming, the temperature of the foaming furnace is controlled to be 170-310° C., and the residence time of the cross-linked mother sheet is 0.5-7 min, so as to obtain a high anti-slip IXPE foam material for electronic screen packaging.

[0012] Preferably, the alkenyl halogenated hydrocarbon in step S2 is an unsaturated halogenated hydrocarbon containing 1 to 2 double bonds and a carbon chain number of 6 to 18.

[0013] The beneficial effects of the present invention are: (1) the product has high anti-slip properties, and the static friction coefficient is above 0.14; (2) The product has antistatic properties, with a surface resistance of less than 108Ω; (3) When the apparent density is less than 0.2 g / cm3, the thickness is 1 mm, the tensile strength is above 1.5 MPa, and the elongation is above 200%; (4) The raw materials are abundant and inexpensive; (5) The prepared materials are widely used in the transportation, packaging and protection of electronic screens; Maleic anhydride grafted elastomer and alkenyl quaternary phosphonium salt are introduced into the polyethylene foam formula. The anti-slip performance of the product is improved by maleic anhydride grafted elastomer, and the anti-static performance of the product is improved by the quaternary phosphonium salt component. The antistatic agent is connected to the polyethylene network by alkenyl, which avoids the migration, precipitation and decay problems of traditional small molecule antistatic agents, greatly guarantees the anti-slip cushioning and anti-static requirements of precision electronic screen packaging, and prepares high anti-slip IXPE foam material for electronic screen packaging. DETAILED DESCRIPTION

[0014] The following is only a preferred embodiment of the present invention, and the protection scope is not limited to this embodiment. All technical solutions under the concept of the present invention should belong to the protection scope of the present invention.

[0015] The invention introduces maleic anhydride grafted elastomer and alkenyl quaternary phosphonium salt into the polyethylene foam material formula as polyethylene foam functional components and compounded with low-density polyethylene, and forms a three-dimensional cross-linked network through radiation cross-linking and high-temperature foaming to prepare a high anti-slip IXPE foam material for electronic screen packaging.

[0016] It should be noted that: (1) The present invention adopts the GB / T 6669 method for determining the compression permanent deformation of soft polymeric materials to determine the compression resilience (25%) of the material.

[0017] (2) The present invention adopts the GB / T10006 plastic film and sheet friction coefficient determination method to determine the static friction coefficient of the material.

[0018] (3) The present invention adopts GB / T 3682-2000 for the determination of the mass flow rate and volume flow rate of thermoplastic melt to test the melt index.

[0019] (4) The present invention adopts the GB / T1033-1986 plastic density and relative density test method to test material density.

[0020] (5) The present invention adopts GB / T 15738 Conductive and antistatic fiber reinforced plastics resistivity test method to test the surface resistance of the material.

[0021] (6) The present invention adopts the method for determining the tensile strength and elongation at break of flexible foam polymer materials in accordance with GB / T 6344 to test the mechanical properties of the material.

[0022] The present invention will be further described below through specific embodiments: Step 1 Synthesis of Maleic Anhydride Grafted Elastomer 100 parts by mass of POE, 15 parts by mass of maleic anhydride and 1 part by mass of azobisisobutyronitrile were subjected to internal kneading reaction in an internal mixer at 130° C. for 2 hours, and then pelletized and extruded to obtain a maleic anhydride grafted elastomer.

[0023] Step 2 Synthesis of alkenyl quaternary phosphonium salt After heating tributylphosphine and dodecenyl chloride in an equal molar ratio at 120° C. for 8 hours, the mixture is filtered, washed with ethyl acetate and dried to obtain the corresponding alkenyl quaternary phosphonium salt antistatic component.

[0024] Step 3 Polyethylene foam preparation Maleic anhydride grafted elastomer, alkenyl quaternary phosphonium salt, polyethylene, POE, antioxidant, azodicarbonamide, zinc stearate, etc. are mixed uniformly in a mass ratio of 15:12:80:20:1:5:2, and then added into a single screw extruder for extrusion, and the extrusion temperature is controlled at (95-130°C), the screw speed is 15rpm, and the die head temperature is 125°C to obtain a mother sheet of a certain thickness; then, the mother sheet is passed through an electron accelerator for irradiation cross-linking, and the irradiation dose is controlled to be 30kGy to form a cross-linked polymerization network; finally, the cross-linked mother sheet is placed in a foaming furnace for foaming, and the temperature of the foaming furnace is controlled to be 170-310°C, and the residence time of the cross-linked mother sheet is 0.5 min to obtain a high anti-slip IXPE foam material for electronic screen packaging.

[0025] Surface resistance: 107Ω, static friction coefficient: 0.19, longitudinal tensile strength: 2.3MPa, longitudinal elongation at break: 225%, transverse tensile strength: 1.4MPa, transverse elongation at break: 360%.

[0026] Example 2-Example 4 Except for the different types of maleic anhydride grafted elastomers used, the other conditions and operations were the same as those in Example 1. The results are shown in Table 1 below.

[0027] Table 1 Example 5-Example 7 Except for the different alkenyl halide hydrocarbons used, the other conditions and operations are the same as those in Example 1. The results are shown in Table 2 below.

[0028] Table 2 Example 8-Example 11 Except for the different amount of maleic anhydride grafted elastomer, other conditions and operations are the same as those in Example 1. The results are shown in Table 1 below.

[0029] Table 3 It can be seen from Table 3 that the maleic anhydride grafted elastomer plays an important role in the mechanical properties and anti-slip properties of the product. When the maleic anhydride grafted elastomer is not added, the anti-slip properties of the product are poor, such as Example 8.

[0030] The specific embodiments described above further illustrate the technical problems, technical solutions and beneficial effects solved by the present invention. It should be understood that the above are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A high anti-slip IXPE foam for electronic screen packaging, characterized in that: The material components include the following parts by weight: 40-90 parts low density polyethylene 10-30 parts of maleic anhydride grafted elastomer 10-25 parts of alkenyl quaternary phosphonium salt 10-30 parts thermoplastic elastomer 1 to 5 parts of sensitizer 2-20 parts of azodicarbonamide foaming agent 0.5-4 parts of antioxidants; After the above components are mixed, they are added into a screw extruder for mixing and extrusion to obtain a master sheet; the master sheet is cross-linked by electron irradiation, and after the electron irradiation cross-linking is completed, the obtained material is subjected to high-temperature foaming treatment to obtain a high-anti-slip IXPE foam material for electronic screen packaging.

2. The high anti-slip IXPE foam for electronic screen packaging according to claim 1, characterized in that: The low-density polyethylene is General low-density polyethylene with a density of 0.901~0.922g / cm3 and a melt index of 1~6 g / 10 min, Linear low-density polyethylene with a density of 0.905~0.930g / cm3 and a melt index of 0.3~5g / 10 min, One or more ultra-low density polyethylenes with a density of 0.880-0.910 g / cm3 and a melt index of 0.35 g / 10 min.

3. The high anti-slip IXPE foam for electronic screen packaging according to claim 1, characterized in that: The maleic anhydride grafted elastomer is one or more of EPDM rubber, ethylene-octene copolymer, ethylene-hexene copolymer, ethylene-butene copolymer, ethylene-vinyl acetate copolymer, natural rubber, isobutylene rubber, styrene-butadiene rubber, styrene-butadiene block copolymer, and pentylbenzene block copolymer.

4. The high anti-slip IXPE foam for electronic screen packaging according to claim 1, characterized in that: The antioxidant is Pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate 1,1,3-Tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane, 1,3,5-Trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, Any one or more of butylated hydroxyanisole, butylated hydroxytoluene, propyl gallate, and tert-butylhydroquinone.

5. The method for preparing a highly anti-slip IXPE foam for electronic screen packaging according to claim 1, characterized in that: The sensitizer is one or more of zinc stearate and zinc oxide.

6. The method for preparing a highly anti-slip IXPE foam for electronic screen packaging according to claim 1, characterized in that: The method comprises the following steps: using maleic anhydride grafted elastomer and alkenyl quaternary phosphonium salt functional components to prepare IXPE foam material with high anti-slip and antistatic properties. S1: Synthesis of maleic anhydride grafted elastomer 100 parts of thermoplastic elastomer, 10-20 parts of maleic anhydride and 1 part of azobisisobutyronitrile were mixed in a mixer at 130°C for 2 hours, and pelletized and extruded to obtain a maleic anhydride grafted elastomer; S2: Synthesis of alkenyl quaternary phosphonium salts Tributylphosphine and alkenyl halide in equal molar ratio are heated at 100-150°C, reacted for 4-12 hours, filtered, washed with ethyl acetate and dried to obtain the corresponding alkenyl quaternary phosphonium salt antistatic component; S3: Preparation of polyethylene foam The maleic anhydride grafted elastomer, alkenyl quaternary phosphonium salt, polyethylene, thermoplastic elastomer, antioxidant, azodicarbonamide, zinc stearate, etc. are uniformly mixed in a mass ratio of 10-30:10-25:40-90:10-30:0.5-4:2-20:1-5, and then added into a single screw extruder for extrusion, and the extrusion temperature is controlled to be 95-130°C, the screw speed is 6-25rpm, and the die head temperature is 90-130°C to obtain a mother sheet with a certain thickness; The master sheet is passed through an electron accelerator for irradiation cross-linking, and the irradiation dose is controlled to be 5 to 50 kGy to form a cross-linked polymer network to obtain a cross-linked master sheet; The cross-linked mother sheet is placed in a foaming furnace for foaming, the temperature of the foaming furnace is controlled to be 170-310° C., and the residence time of the cross-linked mother sheet is 0.5-7 min, so as to obtain a high anti-slip IXPE foam material for electronic screen packaging.

7. The method for preparing a highly anti-slip IXPE foam for electronic screen packaging according to claim 6, characterized in that: The alkenyl halogenated hydrocarbon in step S2 is an unsaturated halogenated hydrocarbon containing 1 to 2 double bonds and having 6 to 18 carbon chains.